Next-Generation version of pseudomonas exotoxin a based immunotoxins with reduced immunogenicity for triple negative breast cancer (TNBC) treatment - Mthethwa, Jabulisile (Department of Integrative Biomedical Sciences (IBMS), 2026)
Breast cancer continues to have the highest mortality rate in comparison to other cancer types, with approximately 19.4 million women aged 15 years and older living at risk of being diagnosed with breast cancer in South Africa. Triple-negative breast cancer (TNBC) subtype, which is mainly characterized by a lack of expression of the oestrogen receptor (ER), progesterone receptor (PR) and human epidermal growth factor receptor 2 (HER2), patients do not benefit from current standard treatments since they are based on these absent biomarkers leading to off-targets which results to an adverse side effects in TNBC patients. TNBC subtypes tend to be more common in women younger than age 40, who are Black, or who have a Breast Cancer gene 1 (BRCA1) mutation. The five-year survival rate for TNBC in South Africa is approximately 19.26% and the major causes of this include the late diagnosis of disease, highly aggressive tumor growth, and the early formation of metastases. Therefore, it is crucial than ever to use a multi-targeted precision medicine approach exploiting the differential overexpression of TNBC-specific cell surface receptors. As part of this effort, tumors should be screened and evaluated for therapeutic and prognostic biomarkers that can precisely show the clinicians which treatment plan will work best for their patients. Combining novel immunotherapies with conventional treatment approaches has demonstrated significant promise for improving cancer quality of the patient's life and survival. Although, when it comes to TNBC, these immunotherapies are frequently used as a last option after more traditional treatments have failed such as chemotherapy. Overexpression of zinc transporter (LIV-1) and trophoblast cell surface antigen-2 (trop2) has been implicated in the oncogenesis of TNBC and associated with an unfavorable prognosis. Consequently, the LIV-1 and TROP-2 biomarkers represent a specific target antigen suitable for immunotherapy. In this study, we successfully developed recombinant immunotoxins by fusing an anti- hliv22 and anti-trop2 single chain variable fragment (scFv) antibody to a truncated mutant of Pseudomonas Exotoxin A (ETA') and deimmunized version of (ETA') RG7787, herewith termed (dETA') introducing a cysteine in position R456. Using the bacterial expression vector pMT, functional (scFv)-ETA' and scFv-dETA' were periplasmically expressed under osmotic stress conditions in the presence of compatible solutes. The 72 kDa, His10-tagged fusion proteins were purified using a two- step Immobilised Metal-ion Affinity Chromatography (IMAC). Specific binding of these recombinant immunotoxins to LIV-1- and TROP2-positive breast cancer cell line MCF-7 were confirmed by confocal microscopy in comparison to an antigen-negative control. The introduction of the new mutation in the RG7787 rIT indicates a partial recovery of enzymatic activity with trop2-targeting rITs showing a 1.4-fold reduction in cytotoxic activity, which is a significant improvement when compared with the 4 to13-fold reductions in IC50 values reported for RG7787 in the Alewine study. This is the first report documenting the specific cytotoxicity of a RG7787 recombinant immunotoxins with cysteine (C) mutation in position R456 introduced towards triple- negative breast carcinoma cells, suggesting that liv-1 and trop-2 specific antibody toxins may become valuable therapeutic reagents for the treatment of triple-negative breast cancer in the future.